Fish IRF6 is a positive regulator of IFN expression and involved in both of the MyD88 and TBK1 pathways. (October 2016) - Li, Shun; Lu, Long-Feng; Wang, Zhao-Xi; Chen, Dan-Dan; Zhang, Yong-An
Abstract: Interferon (IFN) regulatory factors (IRF) are the crucial transcription factors for IFN expression, leading host cell response to viral infection. In mammals, only IRF6 is unaffected by IFN expression in the IRF family; however, in fish, a lower vertebrate, whether IRF6 is related to IFN regulation is unclear. In this study, we identified that zebrafish IRF6 was a positive regulator of IFN transcription and could be phosphorylated by both MyD88 and TBK1. First, the transcript level of cellular irf6 was upregulated by treatment with poly I:C (a mimic of viral RNAs), indicating IRF6 might be involved in the process of host cell response to viruses. Overexpression of IRF6 could upregulate IFN promoter activity significantly, meaning IRF6 is a positive regulator of IFN transcription. Subsequently, at the protein regulation level and in the interaction relationship, IRF6 was phosphorylated by and associated with both MyD88 and TBK1. In addition, overexpression of IRF6 activated the transcription of isg15, rig-i and mavs of host cells; meanwhile, the transcripts of p, m and n genes of SVCV were significantly declined in IRF6-overexpressing cells. Taken together, our data demonstrate that fish IRF6 is distinguished from the homolog of mammals by being a positive regulator of IFN transcription and phosphorylated by MyD88 and TBK1, suggesting that differences in the IRF6 regulation pattern exist between lower and higher vertebrates. Highlights: IRF6 is a positive regulator of zebrafish IFNφ1. IRF6 is phosphorylated by and associated with both MyD88 and TBK1. IRF6 upregulates ISGs expression and declines SVCV replication.